SPK Penilaian Kinerja Karyawan Menggunakan Metode SMART Pada PT Bintang Beton Mandala - Natasya Herdiana; Mulyati (PPPM Institut Teknologi Pagar Alam, 2026)
Manual employee performance evaluation processes often lead to issues such as subjectivity, inconsistency, and time inefficiency. This study aims to develop a web-based decision support system for employee performance evaluation using the Simple Multi Attribute Rating Technique (SMART) method. The SMART method is applied to determine criteria weights, calculate utility values, and generate final scores and rankings based on several aspects, namely planning and performance, competence, and integrity. The system is developed using the Laravel framework with Filament as the admin panel and MySQL as the database. System testing is conducted by comparing manual calculation results with system-generated results using data from four employees as the research sample. In addition, system testing is performed to ensure that the calculations are consistent and reliable. The results show that the system produces the same values as manual calculations with a difference of 0, indicating that the implementation of the SMART method is accurate. Furthermore, the system is able to automate the evaluation process, thereby improving efficiency and reducing potential errors compared to manual methods.